Influence of orientations biomimetic units processed by laser on wear resistance of 6082 aluminium alloy. (July 2020) - Zhao, Guoping; Yuan, Yuhuan; Zhang, Peng; Zhou, Ti; Zhou, Hong
Highlights: Bionic surface with various units orientations were prepared on 6082 Al alloy. The unit present superior microstructure and hardness. The wear resistance of Al alloy was increased by 59.47%. An optimal unit orientation was obtained to resist wear. The wear resistance mechanism was analyzed and the stress was simulated. Abstract: Inspired by the wear-resistant non-smooth surfaces distributed with different hard spots in the nature, we used the laser processing technique to processed bionic units with different distributing orientations to simulate biological wear-resistant surface on the surface of 6082 Al alloy. In the study, a series of experiments were conducted including tension tests, wear tests and simulation analysis. The tensile performance and wear resistance of 6082 Al alloy were significantly improved by the bionic units and were maximized at the distributing angle of 30°, as the yield strength, fracture elongation, ultimate tensile strength and wear resistance were also improved respectively. In addition, the influence mechanism on the wear resistance of bionic units was explored.